Data Visualization Application "JIRA" at PT. Jati Piranti Solusindo Using the Metabase: Data Visualization Application "JIRA" at PT. Jati Piranti Solusindo Using the Metabase - Fahrizal Anwar; Iwan Wahyuddin; Deny Hidayatullah (Jurnal Mantik, 2020)
DBMS is always growing rapidly every year. It means, each company has moved to data digitalization, including PT. Jati Piranti Solusindo. This company has an application that is often accessed for corporate projects. A lot of data on the application that makes the Project Management Officer waste more time to read data from one project. To shorten the time of the PMO of PT. Jati Piranti Solusindo, it needed charts that make it easier for them to access project data. Data visualization is a solution for translating abstract data into more visual information. The results of this visualization are effective because the graphic is easy to read, attractive graphics and can be accessed on a web-based basis.